Conditio humana: Erwin W. Straus on his 75. birthday - Baeyer, Walter von; Griffiths, Richard (Springer Berlin Heidelberg, 1966)
Brief -- Letter -- Late Adolescence. A Lying Fallow Period of Consolidation -- Situation, Jetztsein, Psychose -- Immanuel Kant über das Problem der abnormen Persönlichkeit -- Phenomenology and Psychiatry: The Need for a “Subjective Method” in the Scientific Study of Human Behavior -- The Lightness of Fireworks -- Anthropodology: Man A-foot -- On Becoming a Mother -- Three Olympic Champions -- Anthropological Psychology and Behavioristic Animal Experimentation -- Zu Freuds Abhandlung über das Unheimliche -- Über vitale und intentionale Bedeutungsgehalte -- Sense and Sensibility: Notes toward a Psychological Psychology -- Die Entdeckung der ästhetischen Dimension in der Phänomenologie von Erwin Straus -- Wish and Intentionality -- Der Preis eines menschlichen Lebens -- Anonymity and Recognition: Toward an Ontology of Social Roles -- Medicine, Philosophy and Man’s Infirmity -- Der Mensch als fragendes Wesen -- On the Motility of the Ego -- Sinngestalten des Leidens und des Hoffens -- Man as a Responsible Agent.